Opportunistic infection among HIV seropositive cases in Manipal Teaching Hospital, Pokhara, Nepal - Dhungel, BA; Dhungel, KU; Easow, JM; Singh, YI (Kathmandu University Medical Journal, 2009)
Background: Human Immunodeficiency Virus (HIV)/ Acquired Immunodeficiency Syndrome (AIDS) claimed more than 22 million deaths in the past two decades. About 10,000-15,000 Nepalese are expected to die of AIDS related deaths every year in the absence of effective treatment and care. Major cause of mortality and morbidity in HIV infected people is opportunistic infection (OI). Type of pathogen(s) responsible for OI varies from region to region. Objective: This study attempts to find out OI among HIV seropositive patients visiting MTH, Pokhara. Results: Tuberculosis (30%) was found to be most common OI followed by candidiasis (14%). Pulmonary tuberculosis (21.14%) was more common than extra pulmonary tuberculosis (8.92%). Oral candidiasis (8.92%) was more common than oesophageal candidiasis (5.35%). Conclusion: The study findings indicate that immediate and strong action needs to be taken and guidelines and strategies to tackle the HIV AIDS problems are required and should be equally implemented to achieve a decline in the rate of prevalence of HIV. Key words: HIV, AIDS, Opportunistic infection, Tuberculosis doi: 10.3126/kumj.v6i3.1708 Kathmandu University Medical Journal (2008), Vol. 6, No. 3, Issue 23, 335-339